2018
DOI: 10.1007/s10068-018-0493-z
|View full text |Cite
|
Sign up to set email alerts
|

New formulation of vitamin C encapsulation by nanoliposomes: production and evaluation of particle size, stability and control release

Abstract: In the present study, the effects of different ratios of milk phospholipids, cholesterol and phytosterols (Campesterol) powder (50-100%, 0-50%, and 0-50%, respectively) and sonication time (20, 25, 30, 35 and 40 min) were investigated to produce a new formulation of nanoliposomes for encapsulation of vitamin C. The results showed that increasing the time of sonication and decreasing the ratio of phospholipid to phytosterol significantly decreased nanoliposomes' particle size (p \ 0.05). The maximum encapsulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 19 publications
3
15
0
Order By: Relevance
“…The obtained EE for liposomes ranged from 52.35% to 94.18% (Table 1), showing the efficacy of the liposome technique. Both the wall material ratio and sonication process had a statistically significant ( p < 0.05) effect on the EE of VC (Table A1), which was similar to the result obtained by Amiri et al (2019). From Table 1, it can be observed that increasing the SA content or replacing PC with SA resulted in a decrease in the EE.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The obtained EE for liposomes ranged from 52.35% to 94.18% (Table 1), showing the efficacy of the liposome technique. Both the wall material ratio and sonication process had a statistically significant ( p < 0.05) effect on the EE of VC (Table A1), which was similar to the result obtained by Amiri et al (2019). From Table 1, it can be observed that increasing the SA content or replacing PC with SA resulted in a decrease in the EE.…”
Section: Resultssupporting
confidence: 88%
“…Considering the effectiveness of plant‐based sterol over cholesterol, Hsieh et al (2002) and Chan et al (2004) presented better EE and stability in liposomes with SA and phytosterol than those prepared with cholesterol. Amiri et al (2019) reported the highest EE of 73.65% for a ratio of 75:25 phospholipid and phytosterol, whereas with cholesterol, the EE was 58.54%. However, in the present study, the subsequent reduction in VC entrapment with the addition of SA at different ratios may be a consequence of permeability modification or changes in packing density with SA, as explained in Raffy and Teissié (1999) and Soto‐Arriaza et al (2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamins (ascorbic acid and α-tocopherol), spices (cinnamon, cloves, nutmeg, ginger, black pepper, and garlic), herbs (rosemary, oregano, marjoram, sage, and basil), and plant extracts (tea, grape seed, cranberry, blueberry, and strawberry) contain antioxidant ingredients (Ahmad et al, 2015;Amiri et al, 2019b). The antioxidant role of plant extracts is because they contain phenolic acids (gallic, protocatechuic, caffeic, and rosmarinic acids), phenolic diterpenes (carnosol, carnosic acid, rosmanol, and rosmadial), flavonoids (quercetin, catechin, naringenin, and kaempferol), and volatile oils (eugenol, carvacrol, thymol, and menthol).…”
Section: Plant-based Antioxidant Agentsmentioning
confidence: 99%
“…It was seen that formulation TEI-1 and TTFH-1 showed lowest tamoxifen entrapment efficiency due to the lowest level of phosphatidylcholine and cholesterol in the formulation. On the other hand, TEI-9 and TTFH-9 revealed highest tamoxifen entrapment efficiency because of highest amount of phosphatidylcholine and cholesterol present in the formulation for both methods [30].…”
Section: Percent Drug Entrapment Efficiency (%Dee) Of Liposomesmentioning
confidence: 95%